Ibaloy notions of homeland from memories of place: an oral history of Loakan, Baguio City - Bahni, Rosella Camte-
This study analysed oral sources to situate memories of place that shaped Ibaloy notions of homeland which were evaluated to determine their implications to the Ibaloy homeland in Loakan. It is a qualitative research conducted among Ibaloys in Loakan, Baguio City using adivay as an indigenous method, oral history and ethnographic methods to gather data from memories of place and supplemented by documentary sources. Men1ories of place were analyzed using humanist geography, interpretive and indigenous approaches.